2015
DOI: 10.1111/mmi.13218
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori strains vary cell shape and flagellum number to maintain robust motility in viscous environments

Abstract: Summary The helical shape of the human stomach pathogen Helicobacter pylori has been suggested to provide mechanical advantage for penetrating the viscous stomach mucus layer. Using single-cell tracking and quantitative morphology analysis we document marked variation in cell body helical parameters and flagellum number among H. pylori strains leading to distinct and broad speed distributions in broth and viscous gastric mucin media. These distributions reflect both temporal variation in swimming speed and mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
147
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(161 citation statements)
references
References 77 publications
14
147
0
Order By: Relevance
“…While initial studies suggested that like B. burgdorferi, H. pylori cell shape mutants showed swimming behavior similar to that of the wild type in methylcellulose viscous solutions (19), single-cell tracking of mul-tiple H. pylori strains revealed large temporal fluctuations in the speed of individual bacteria that may have confounded prior studies (65). Analysis of 50 to 100 cells per genotype revealed contributions of both helical shape and increased flagellar number to swimming speed in viscous gastric mucin solutions, in addition to an enhanced ability to escape from a mucin gel (65). Further work on motility specifically at physiologic concentrations of gastric and intestinal mucins, combined with exploration of the localization of helical versus nonhelical mutants within the infected host, will be needed to definitively establish the mechanism(s) by which nonhelical mutants of H. pylori and C. jejuni fail to robustly colonize their hosts.…”
Section: Corkscrews and Wavesmentioning
confidence: 92%
See 2 more Smart Citations
“…While initial studies suggested that like B. burgdorferi, H. pylori cell shape mutants showed swimming behavior similar to that of the wild type in methylcellulose viscous solutions (19), single-cell tracking of mul-tiple H. pylori strains revealed large temporal fluctuations in the speed of individual bacteria that may have confounded prior studies (65). Analysis of 50 to 100 cells per genotype revealed contributions of both helical shape and increased flagellar number to swimming speed in viscous gastric mucin solutions, in addition to an enhanced ability to escape from a mucin gel (65). Further work on motility specifically at physiologic concentrations of gastric and intestinal mucins, combined with exploration of the localization of helical versus nonhelical mutants within the infected host, will be needed to definitively establish the mechanism(s) by which nonhelical mutants of H. pylori and C. jejuni fail to robustly colonize their hosts.…”
Section: Corkscrews and Wavesmentioning
confidence: 92%
“…However, the localized production of urease by H. pylori actually changes the viscoelastic properties of the surrounding mucus from a gel-like state to a viscous solution, thus challenging the corkscrew model (61). While initial studies suggested that like B. burgdorferi, H. pylori cell shape mutants showed swimming behavior similar to that of the wild type in methylcellulose viscous solutions (19), single-cell tracking of mul-tiple H. pylori strains revealed large temporal fluctuations in the speed of individual bacteria that may have confounded prior studies (65). Analysis of 50 to 100 cells per genotype revealed contributions of both helical shape and increased flagellar number to swimming speed in viscous gastric mucin solutions, in addition to an enhanced ability to escape from a mucin gel (65).…”
Section: Corkscrews and Wavesmentioning
confidence: 94%
See 1 more Smart Citation
“…Thus, during infections, as well as the transmission by the nasogastric tube, H. pylori entered a stomach without acid, allowing the bacterium to bury into the mucous layer before normal gastric acidity was reestablished. In most cases of chronic H. pylori gastritis, there is no information of any symptomatic episode (Martínez et al, 2016).…”
Section: Acute Infection By Helicobacter Pylorimentioning
confidence: 99%
“…Cultures are incubated under microaerobic conditions (85% N2, 10% CO 2 , 5% O 2 ) at 35 to 37ºC for at least 7 d before discarding cultures as negative. Morphological characteristics and positive catalase, oxidase, and urease reactions are used for identification of H. pylori (Martínez et al, 2016).…”
Section: Helicobacter Pylori Infectionmentioning
confidence: 99%